Identifying keystone habitats with a mosaic approach can improve biodiversity conservation in disturbed ecosystems. (11th September 2017) - Hitchman, Sean M.; Mather, Martha E.; Smith, Joseph M.; Fencl, Jane S.
Abstract: Conserving native biodiversity in the face of human‐ and climate‐related impacts is a challenging and globally important ecological problem that requires an understanding of spatially connected, organismal‐habitat relationships. Globally, a suite of disturbances (e.g., agriculture, urbanization, climate change) degrades habitats and threatens biodiversity. A mosaic approach (in which connected, interacting collections of juxtaposed habitat patches are examined) provides a scientific foundation for addressing many disturbance‐related, ecologically based conservation problems. For example, if specific habitat types disproportionately increase biodiversity, these keystones should be incorporated into research and management plans. Our sampling of fish biodiversity and aquatic habitat along ten 3‐km sites within the Upper Neosho River subdrainage, KS, from June‐August 2013 yielded three generalizable ecological insights. First, specific types of mesohabitat patches (i.e., pool, riffle, run, and glide) were physically distinct and created unique mosaics of mesohabitats that varied across sites. Second, species richness was higher in riffle mesohabitats when mesohabitat size reflected field availability. Furthermore, habitat mosaics that included more riffles had greater habitat diversity and more fish species. Thus, riffles (<5% of sampled area) acted as keystone habitats. Third, additional conceptual development, which we initiate here, can broaden the identification of keystone habitats across ecosystems and further operationalize this concept for research and conservation. Thus, adopting a mosaic approach can increase scientific understanding of organismal‐habitat relationships, maintain natural biodiversity, advance spatial ecology, and facilitate effective conservation of native biodiversity in human‐altered ecosystems. Abstract : Conserving native biodiversity in the face of human‐altered ecosystems is a challenging and globally important ecological problem. A mosaic approach (where connected, interacting collections of habitat patches are examined) provides a scientific foundation for addressing ecologically‐based conservation problems. For example, if specific habitat types disproportionately increase biodiversity, these keystones should be incorporated into research and management plans. Sampling of fish biodiversity and aquatic habitat within the Upper Neosho River sub‐drainage, KS, helped identify keystone habitats. Species richness was higher in riffles when mesohabitat size reflected field availability. Furthermore, habitat mosaics that included more riffles had greater habitat diversity and more fish species. Thus, riffles (<5% of sampled area) acted as keystone habitats. Additional conceptual development can broaden the identification of keystone habitats across ecosystems and further operationalize the keystone habitat concept. Adopting a mosaic approach to identify keystone habitats can increase scientific understanding of organismal‐habitat relationships and maintain biodiversity.